(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the effect of a proposed strategy in developing the skills of preparing an educational film according to the semiotic approach using the mobile phone among art education teachers. The researchers adopted the experimental method to implement their procedures as it is more appropriate for achieving the objectives of the current research, which aims to study the effect of an independent variable on a dependent variable. The research included a method for preparing an educational film according to the semiotic approach. The purpose of this is to train teachers to prepare purposeful educational films directed to learners.